A model for wildfire prevention planning in game resources (Ecological Modelling, 2010)
The high incidence of hunting activity and forest ﬁres in different ecosystems (particularly in Mediterranean ecosystems) requires a model, which allows for the comprehensive management of hunting resources and estimating the potential damage caused by this type of disturbance. This paper proposes a model for evaluating the socio-economic effects of forest ﬁres on hunting. Its cornerstone lies in evaluating hunting resource availability for each ecosystem within its territorial mosaic. Each game management unit (GMU) is identiﬁed by vegetation structure and habitat type. It presents a novel approach in which the economic value of each game management unit is linked to potential forest ﬁre damages. The effect a forest ﬁre has on an entire ecosystem depends on the intensity of its ﬂames. A sample study was undertaken in the province of Huelva in Andalusia (southern Spain). The socio-economic hunting vulnerability of the province of Huelva was 45,188,000D . The results obtained conﬁrmed the need for an economic appraisal of non-forest products in the forest and other woodland areas. Geographic Information System increases the ﬂexibility and simplicity of our methodology which permits immediate extrapolation to other agroforestry territories.